2012
DOI: 10.2478/v10266-012-0087-9
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Absorption by Used Moulding and Core Sands

Abstract: The paper presents measurement results of standing wave ratio to be used as an efficiency indicator of microwave absorption by used moulding and core sands chosen for the microwave utilization process. The absorption measurements were made using a prototype stand of microwave slot line. Examined were five used moulding and core sands. It was demonstrated that the microwave absorption measurements can make grounds for actual microwave utilization of moulding and core sands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The issues of applying SHF radiation in technical systems, including transport, are covered in [8][9][10][11]. Analysis of available publications shows that as for the efficiency of warming-up and, to a greater extent, maintaining the optimum temperature of TF the given method is the most competitive.…”
Section: Using Shf Radiation For Technological Fluids Preheatingmentioning
confidence: 99%
“…The issues of applying SHF radiation in technical systems, including transport, are covered in [8][9][10][11]. Analysis of available publications shows that as for the efficiency of warming-up and, to a greater extent, maintaining the optimum temperature of TF the given method is the most competitive.…”
Section: Using Shf Radiation For Technological Fluids Preheatingmentioning
confidence: 99%
“…Research on microwave drying of molding sand with bentonite [9,13] showed that it is possible not only to shorten the process time (even 10 times), but also to improve its properties. The compressive and shear strength is higher by 20-35% and 5-10%, respectively, than that of conventionally dried masses.…”
Section: Introductionmentioning
confidence: 99%
“…Of key importance in the microwave drying process is the selection of appropriate parameters: radiation power and heating time. During too intensive microwave drying, the increasing pressure inside the material, especially when the phase it contains turns into a gas state, with limited permeability, may lead to deformation or even destruction of the product [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many domestic and foreign research centres, studies are carried out to mitigate the negative characteristics of foundry sands with water glass [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%